(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Myopia is one of the important causes of visual impairment worldwide. The two most common refractive surgeries for myopia treatment are LASIK (Laser-Assisted In-Situ Keratomileusis) and PRK (Photorefractive Keratectomy). Purpose. This study investigates the efficacy and safety of LASIK and PRK for Myopia correction. Methods. A systematic review was conducted following PRISMA 2020 guidelines across PubMed, Cochrane, and ScienceDirect databases through December 2024. The quality and bias of studies were assessed using the assessment tool developed by the Effective Public Health Practice Project. The data were summarized using odds ratios (OR) with 95% confidence intervals (CI) and mean differences to determine the efficacy and safety of LASIK and PRK for myopia. Result. Nine randomized controlled trial studies from 1998 to 2014 were included, involving 698 eyes with any degree of myopia. The meta-analysis found no significant difference in the proportion of eyes achieving uncorrected visual acuity of 20/20 at 6 months (pooled OR, 0.84; 95% CI, 0.53-1.34; P = 0.47) and 12 months (pooled OR, 1.11; 95% CI, 0.62-2.01; P = 0.72). LASIK and PRK were equally effective for the proportion of eyes achieving within ± 0.50 D of target refraction at 12 months (OR, 1.00; 95% CI, 0.40–2.51; P = 1.00). Loss of 2 lines of best corrected visual acuity at 6 months was less frequent with LASIK (OR, 2.41; 95% CI, 0.73-7.18; P = 0.15). It was found that both LASIK and PRK interventions did not have a significant difference in postoperative mean spherical equivalent until 1 year of follow-up (0.07; 95% CI, 0.05-0.19; I2 = 16%). Conclusions. Efficacy, safety and visual outcomes of LASIK for myopia are similar to those achieved with PRK.